Financial Soundness Indicators-Experience with the Coordinated Compilation Exercise and Next Steps. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
Overview. This paper reports on the experience with the work program on Financial Soundness Indicators (FSIs) and offers proposals for taking forward the work on FSIs. The work program aimed at (i) increasing member countries' FSI compilation capacity and supporting their compilation efforts; (ii) expanding reporting and analysis of FSIs in the work of the Fund; and (iii) undertaking further analytical work on FSIs. In this context, a Coordinated Compilation Exercise (CCE) for FSIs was conducted, and experience was gained with the use of FSIs in Article IV surveillance, the Financial Sector Assessment Program (FSAP), and the interdepartmental Vulnerability Exercise (VE). The paper proposes that the Fund aintains an ongoing role in collecting and disseminating FSIs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet